Enhancing the Effect of PD-1/L1 Blockers by Polarizing M2 Tumor-associated Macrophages (TAMs) - Zhang, Xinyan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The cancerous microcosm, known as the tumor micro-environment (TME), encompasses a highly intricate network where a multitude of cells and their emitted substances significantly contribute to the development and advancement of malignant growths. The role of TAMs in the TME has been increasingly valued. Owing to its significant plasticity, it typically divides into pro-inflammatory M1 and anti-inflammatory M2. Within TME, TAMs typically show polarization towards M2. Antibodies are used by PD-1/L1 blockers to prevent PD-1 and PD-L1 from binding, aiming to reduce tumor symptoms. Presently, the efficacy of this medication is limited to a select few patients, in contrast to other patients who exhibit a level of resistance to the drug. Latest research indicates that M2 TAMs exert a suppressive influence on the PD-1/L1 blockade treatment. This substance suppresses the growth and penetration of CD8+T cells and generates Indole 2,3-dioxygenase (IDO), resulting in resistance to PD-1/L1 inhibitors and facilitating the multiplication and evasion of cancer cells. Some studies have reduced the resistance to PD-1/L1 blockers and promoted the treatment of tumors by polarizing TAMs. The dissertation compiles identified TAMs polarization routes and the impact of M2 TAMs on PD-1/L1 inhibitors. The discussion also encompasses present-day techniques for directing M2 TAMs towards the M1 type and advocating these approaches on PD-1/L1 blockers.